The Diagnostic Performance of 18F-PSMA-1007 PET/CT in Prostate Cancer Patients with Early Recurrence after Definitive Therapy with a PSA <10 ng/ml - Lengana, Thabo; Lawal, Ismaheel; Janse Van Rensburg, Charl; Mokoala, Kgomotso; Moshokoa, Evelyn; Mazibuko, Sfiso; Van de Wiele, Christophe; Maes, Alex; Vorster, Mariza; Sathekge, Mike Machaba (Nuklearmedizin - NuclearMedicine, 2022)
Aim The prostate bed is one of the common sites of early recurrence of prostate cancer. The currently used PSMA ligands (68Ga-PSMA-11 and 99mTc-PSMA) undergo early urinary clearance resulting in interfering physiological activity within and surrounding the prostate. This can result in sites of cancer recurrence being obscured. 18F-PSMA-1007 has an advantage of delayed urinary clearance thus the prostate region is reviewed without any interfering physiological activity. The aim of this study was to determine the diagnostic performance of 18F-PSMA-1007 PET/CT in patients with early biochemical recurrence after definitive therapy.Methods Forty-six Prostate cancer (mean age 66.7±7.5, range 48–87 years) presenting with biochemical recurrence (median PSA 1.6ng/ml, range 0.1–10.0) underwent non-contrast-enhanced 18F-PSMA-1007 PET/CT. PET/CT findings were evaluated qualitatively and semiquantitatively (SUVmax) and compared to the results of histology, Gleason grade, and conventional imaging.Results Twenty-four of the 46 (52.2%) patients demonstrated a site of recurrence on 18F-PSMA-1007 PET/CT. Oligometastatic disease was detected in 15 (32.6%) of these patients. Of these 10 (37.5%) demonstrated intra-prostatic recurrence, lymph node disease was noted in 11 (45.8%) whilst two patients demonstrated skeletal metastases. The detection rates for PSA levels 0–<0.5, 0.5–<1, 1–2, >2 were 31.3%, 33.3%, 55.6% and 72.2% respectively. 7 (29.2%) of the positive patients had been described as negative or equivocal on conventional imaging. An optimal PSA cut-off level of 1.3ng/ml was found.Conclusion18F-PSMA-1007 demonstrated good diagnostic performance detecting sites of recurrence. Its ability to detect sites of recurrence in the setting of early biochemical recurrence will have a significant impact on patient management.
Keywords: 18F-PSMA-1007 PET/CT; 68Ga-PSMA-11 PET/CT; biochemisches Rezidiv; Prostatakarzinom